2002
DOI: 10.1159/000057590
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lactate and Other Ions in Plaque and Saliva after a Fluoride Rinse and Subsequent Sucrose Administration

Abstract: The purpose of this study was to examine plaque and saliva composition after a fluoride rinse and subsequent sucrose application. Fifteen subjects accumulated plaque for 48 h, and then rinsed with a fluoride rinse based on 228 µg/g (ppm) Na2SiF6 and some received no rinse. After 60 min, upper and lower buccal molar plaque samples and 1-min saliva samples were collected. The subjects then rinsed with 10% g/g sucrose solution, and 7 and 15 min later, a second and a third set of samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
7
26
1
3
Order By: Relevance
“…Though a previous study has reported that an experimental 228 mg/kg F 'controlled release' F rinse given, as in the current study, 1 h before sucrose rinse significantly reduced lactate production and increased plaque pH [Vogel et al, 2002], no additional suppression of metabolic acids was observed from the 100 mg/kg fluoride in the current study. Previous studies have also found that fluoride did not increase the antiglycolytic effects of antimicrobial rinses [Giertsen and Scheie, 1995].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Though a previous study has reported that an experimental 228 mg/kg F 'controlled release' F rinse given, as in the current study, 1 h before sucrose rinse significantly reduced lactate production and increased plaque pH [Vogel et al, 2002], no additional suppression of metabolic acids was observed from the 100 mg/kg fluoride in the current study. Previous studies have also found that fluoride did not increase the antiglycolytic effects of antimicrobial rinses [Giertsen and Scheie, 1995].…”
Section: Discussioncontrasting
confidence: 61%
“…Effective suppression of plaque metabolic acid production may be an important approach for prevention or reduction of dental caries and gingivitis. Although fluoride is an effective anticaries agent, the reported clinical effect by fluoride on plaque metabolic activity was somewhat contradictory [Giertsen and Scheie, 1995;Hamilton, 1990;Vogel et al, 2002]. Chlorhexidine-based antimicrobial mouthrinses, however, have been shown to reduce plaque acid production and to increase the postsucrose minimum pH [Giertsen and Scheie, 1995].…”
mentioning
confidence: 99%
“…The inherent buffering capacity of both plaque [Shellis and Dibdin, 1988] and stimulated saliva [Edgar et al, 1994] also need to be considered in determining the pH achieved, rather than the concentrations of acid anions formed, when assessing the cariogenic potential of a food item in an model system. Here we did not measure plaque acid concentrations but these will be significantly higher than those found in saliva [Vogel et al, 2002]. The clinical relevance of which is that the fall in plaque pH accompanying the production of these acids may persist longer at interproximal sites in particular, since salivary access and consequent dilution and buffering will be limited.…”
Section: Discussionmentioning
confidence: 90%
“…The major acids produced were lactate and succinate, only low and variable concentrations of formate were detected and the salivary concentration of acetate diminished immediately following consumption of the fruits or the glucose rinse. No other acids were monitored in the saliva although other investigators have quantified the concentrations of other longer chain acids [Luke et al, 1999;Vogel et al, 2002]. The production of lactate occurs when streptococci are exposed to high sugar concentrations and mixed fermentation end products, including acetate, formate and ethanol, are produced in conditions of low sugar concentration [Yamada and Carlsson, 1975].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride inhibits demineralization and promotes remineralization of the tooth surface (ten Cate, 1999;Fejerskov, 2004). Fluoride is also known to inhibit bacterial acid production in vitro (Hamilton, 1990;Marquis, 1990;Jenkins, 1999) and plaque acid production in vivo (Tatevossian, 1990;Vogel et al, 2002). Competitive inhibition by fluoride of enolase, an enzyme in the Embden-Meyerhof-Parnas pathway (the EMP pathway) extracted from Streptococcus mutans and other plaque bacteria (Kaufmann and Bartholmes, 1992;Guha-Chowdhury et al, 1997), suggested that enolase is the target enzyme by fluoride inhibition.…”
Section: Introductionmentioning
confidence: 99%